(3cJGH HGdWHs - (3GdjGaYj , Yaja GdOjf YHO Gddg Hf CSYO Hf Ydj GdjGaYj Gdjefj, Yaja GdOjf,J (B768 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi YRJ YRJg ChdkG hCNQkG hHYO agPG cJGH fajSi eLehY HGdWH hjLH Ydi GdEfSGf Cf dGjTQH YbH GdLeGY aEfg jQVi GdCYVGA s
(3BNQgG (B:s
(3aGFOI dJaJjJ GdMUi hjfRd ai GdTeS KdGKI CjGe hcd SGYI JWd Ydjge EPG fTa JZeQge Edi JeGe GdKdGKI CjGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B72 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B34s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdWHs